EVALUATING THE FOOD SERVICE ATTRIBUTES OF PONDOK HIJAU RESTAURANT - Palimbongan, Reynalda C. M.; Massie, James D. D.; Saerang, Regina T. (Universitas Sam Ratulangi, 2021)
This study aims to know the importance and performance of Food Service Attributes in Pondok Hijau Restaurant. Respondents in this study amounted to 100 customer who visits this restaurant. Using Importance and Performance Analysis (IPA). The results of this study shows that Service is located in quadrant I (Concentrate Here). This means that this attribute is perceived to be importance to customer and the performance level are fairly low. Employee, Freshness and Design and Decor are located in quadrant II (Keep up the good work). Attributes that located in Quadrant II means that it has a high importance to the customer and the company also achieves high performance according to the customer. Appearance and Variety are located in quadrant III (Low Priority), this means that the two attributes are not really importance for the consumer and at the same time also has the low performance level. Presentation and Cleanliness are located in quadrant IV (Possible Overkill), it means this contains attributes of low importance, but where performance is relatives high. The importance low because consumer think that the Presentation and Cleanliness is not really matter. Pondok Hijau should consider which attributes need to be developed or which attributes need to keep the performance based on the result in quadrant, so the consumer will satisfy with the resto. Keywords: food service attributes, importance and performance analysis, restaurant.